Open PLC: an Open Source Solution For Training Of Non Maintenance Staff - Yani Koerniawan; Rinaldi Rinaldi (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Programmable Logic Controllers (PLCs) are essential in modern industrial automation and Industry 4.0 environments. However, in many vocational institutions and industrial training centers, PLC access is limited primarily to maintenance departments due to high hardware costs, proprietary software licensing, and restricted system flexibility. This limitation reduces opportunities for non-maintenance staff, students, and interdisciplinary engineering practitioners to develop practical automation competencies. To address this gap, a community service program was conducted at Akademi Komunitas Toyota Indonesia, Karawang, utilizing OpenPLC—an open-source, IEC 61131-3–compliant PLC platform—as a low-cost and flexible training solution. The program involved structured workshops, hands-on practical sessions, and project-based learning activities using affordable hardware such as Arduino and Raspberry Pi. Participants were trained to design, simulate, and implement basic control systems, as well as integrate PLC logic with IoT and simple SCADA environments. The results demonstrate that OpenPLC effectively improves participants’ understanding of PLC programming concepts and enhances their practical skills in automation system development. The open-source nature of the platform reduces financial barriers while enabling broader experimentation beyond maintenance-oriented applications. This initiative shows that OpenPLC can serve as an accessible and sustainable training tool to expand industrial automation competencies across non-maintenance domains.